Leaf sponge tool use by Buraiga chimpanzees, Pan troglodytes schweinfurthii, in Kibale National Park, Uganda - Edwards, Wren I.; Guma, Nelson; Agaba, Hillary; Balyesiima, Godfrey; Asalu, Edward; Rothman, Jessica; Stevens, Nancy J. (African Journal of Ecology, 2023)
Chimpanzees (Pan troglodytes) are avid tool users, although tool uses and functions vary among communities. Some chimpanzees use stones or wood in extractive forag- ing to crack open nuts, whereas others use long stems to consume termites or ants. Leaf sponges are versatile and widespread tools used by chimpanzees, created by crumpling leaves in the mouth and then using the hands to immerse the tool to pro- cure liquids from difficult-to-access locations. Here we describe leaf sponge use by two female chimpanzees in Kibale National Park, Uganda, documenting for the first time tool use in the Buraiga chimpanzee community.
Keywords: Buraiga; Extractive foraging; Leaf sponge; Primatology; Tool use